2023
DOI: 10.3390/nano13152256
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Ablative Synthesis of Silicon–Iron Composite Nanoparticles for Theranostic Applications

Abstract: The combination of photothermal and magnetic functionalities in one biocompatible nanoformulation forms an attractive basis for developing multifunctional agents for biomedical theranostics. Here, we report the fabrication of silicon–iron (Si-Fe) composite nanoparticles (NPs) for theranostic applications by using a method of femtosecond laser ablation in acetone from a mixed target combining silicon and iron. The NPs were then transferred to water for subsequent biological use. From structural analyses, it was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…In this nano era, nanotechnologies and the related nanomaterials have demonstrated their powers in almost all the applied scientific fields [6,7], including numerous biomedical treatments [8][9][10][11][12][13][14]. Those nano-related elements are bringing out revolutionary changes in the field of orthopedics for orthopedic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In this nano era, nanotechnologies and the related nanomaterials have demonstrated their powers in almost all the applied scientific fields [6,7], including numerous biomedical treatments [8][9][10][11][12][13][14]. Those nano-related elements are bringing out revolutionary changes in the field of orthopedics for orthopedic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Special Issue was focused on recent trends in the fabrication of functional nanostructures, nanomaterials and nanotextured surfaces using laser radiation. The resulting content of this Special Issue comprising 10 original papers reflects the diversity of the developing nanofabrication strategies that utilize pulsed laser radiation, including pulsed laser ablation in liquid (PLAL) for nanomaterial generation [ 1 , 2 , 3 , 4 ], pulsed laser deposition (PLD) of functional coatings [ 5 ], laser-induced forward transfer (LIFT) [ 6 ], laser sintering [ 7 ], pulsed laser surface nanotexturing [ 8 ] and direct laser writing in transparent media [ 9 , 10 ].…”
mentioning
confidence: 99%
“…A perfect example of expanded functionality originating from a combination of different materials within unified nanoparticles was given by Bubnov et al, who reported on PLAL-based synthesis of silicon–iron (Si-Fe) nanohybrids [ 1 ]. In particular, the authors demonstrated that such a material combination is favorable for the spectrally strong broadband light-to-heat conversion performance of the produced nanoparticles, while the presence of Fe atoms provides them with magnetic properties.…”
mentioning
confidence: 99%